Dream on : a novel - Hockman, Angie (Gallery Books, 2022)
"The author of the "absolutely sparkling debut" (Entertainment Weekly) Shipped returns with a fresh romantic comedy following a law student who wakes up from a car accident with memories of a boyfriend she's never met, only to run into him in a flower shop a year later. But when she finds herself having feelings for her dream man's brother--the owner of said flower shop--things start to get a lot more complicated"--